Long-term survival in patients undergoing trans jugular intrahepatic portosystemic shunt placement after liver transplantation. (March 2023) - Leonardi, F.; Pasulo, L.; Mangia, G.; Triolo, M.; Iegri, C.; Luca', M.G.; Agazzi, R.; Marra, P.; Pinelli, D.; Colledan, M.; Fagiuoli, S.
Abstract : Introduction: Trans jugular Intrahepatic Portosystemic Shunt (TIPS) insertion after liver transplantation (LT) has been reported in a limited number of patients, with controversial results. The absence of long-term survival studies has not allowed the clear definition of a prognosis of these patients. This study aims at evaluating the long-term graft- and patient-survival in this subset of patients. Methods: Patients receiving a TIPS for post-LT portal hypertension- or venous-related complications in our Transplant Center were retrospectively evaluated. Clinical success was defined as the resolution of the complication that led to the TIPS insertion. Procedure-related complications were documented. Patients' follow up was defined until death or at June 30 th 2020. Results: Between 2001 and 2015, 25 LT patients and 2 re-LT patients underwent TIPS insertion. Patients were more frequently males (77.8%), with a median age at LT (or re-LT) of 52 years (range 24-69) and predominantly viral aethiology (74.1%). TIPS placement was performed after a median of 91 days (27-787) following LT. The more frequent indications for post-LT TIPS insertion were Veno-Occlusive Disease-related ascites (48.2%), non-VOD ascites (33.3%), portal vein thrombosis (7.4%). Mean pre-TIPS MELD-score was 12.5±4.4; mean HVPG was 16.1±6.5 mmHg pre-TIPS and 7.9±4.1 mmHg post-TIPS. Clinical success was achieved in 20 patients (74.1%). The rate of procedure-related complications was 40.7%, no procedure-related deaths occurred. During the follow-up, 12 patients (44.4%) developed at least one episode of encephalopathy, shunt occlusion was recorded in 8 patients (29.6%). Graft- and patient-survival rates at 1, 3 and 5 years post-TIPS were 77.8%, 63.0%, 44.4% and 85.2%, 74.1%, 55.6% respectively. Graft-survival rates were greater in patients with pre-TIPS MELD<14 (75.0% and 56.3% at 3 and 5 years; p=0.028). Conclusions: Patients undergoing TIPS insertion after LT showed a 5-year graft survival post-TIPS of nearly 45%; therefore they need a careful follow-up for a possible re-transplantation candidacy.